1983
DOI: 10.1128/jb.154.1.118-129.1983
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of mitochondrial protein synthesis in sporulation: effects of erythromycin on macromolecular synthesis, meiosis, and ascospore formation in Saccharomyces cerevisiae

Abstract: MATERIALS AND METHODS Strains. The relevant genotype of S. cerevisiae Z270 and the map distances are shown in Fig. 1. This strain was kindly supplied by M. S. Esposito, Donner Laboratory, University of California. Erythromycin-resistant derivatives of strain Z270 were isolated as colo-118

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…It was also reported that ASA inhibits b-oxidation (Glasgow et al, 1999;Deva et al, 2001). Strikingly, ascosporogenesis in Saccharomyces cerevisiae occurs only in the presence of mitochondrial respiration (Marmiroli et al, 1983). Consequently, it is now important to determine whether this is also true in Dipodascus geniculatus and other yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that ASA inhibits b-oxidation (Glasgow et al, 1999;Deva et al, 2001). Strikingly, ascosporogenesis in Saccharomyces cerevisiae occurs only in the presence of mitochondrial respiration (Marmiroli et al, 1983). Consequently, it is now important to determine whether this is also true in Dipodascus geniculatus and other yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above, aspirin may also inhibit mitochondrial activity by uncoupling mitochondrial oxidative phosphorylation and/or inhibiting electron transport (Somasundaram et al 1997;Norman et al 2004). It is therefore not surprising that the yeast sexual cycle, which has previously been found to be dependent on mitochondrial activity (Marmiroli et al, 1983;Codon et al, 1995), is more susceptible to aspirin than are asexual vegetative cells (Kock et al, 2003). This is particularly true for Ascoidea, Dipodascopsis, Dipodascus and Eremothecium, in which high mitochondrial activity is presumably necessary to produce sufficient energy through aerobic respiration to sustain high production and assembly throughput during the formation of numerous ascospores within a single enlarged sexual cell.…”
Section: Functions Of 3-oh Oxylipinsmentioning
confidence: 99%
“…compared 2‐DE patterns of yeast in sporulation medium with the patterns of vegetatively growing cells; 11 proteins were induced in sporulation medium and 9 proteins specific to vegetative growth were visualised 19. Subsequent work confirmed a novel pattern of protein synthesis during sporulation and also demonstrated that mitochondrial protein synthesis is necessary for the expression of some sporulation‐specific polypeptides and for the sporulation process to occur 5, 17, 20. Although the 2‐DE approach permitted a global proteomic analysis, this early work did not investigate the temporal patterns of protein expression levels and identification of the differentially expressed gel features was not undertaken.…”
Section: Introductionmentioning
confidence: 96%
“…Early studies indicated that protein synthesis is required for initiation and completion of spore formation and also necessary for certain events which are restricted to the sporulation process 15–17. Cytological observation of structures unique to sporulating cells suggested that specialised meiotic proteins might exist 18.…”
Section: Introductionmentioning
confidence: 99%